Pemasaran Politik Dewan Pimpinan Cabang Partai Persatuan Pembangunan Kota Tangerang Pada Pemilu 2019 - Triwibawa, Adhe Taufiq Harry; Fuad, Anis; Mayrudin, Yeby Ma’asan (International Journal of Demos (IJD), 2023)
AbstractThis study illustrates the political marketing strategy of the United Development Party (DPC) of the United Development Party (PPP) Board in winning the election contestation, political marketing carried out by the United Development Party is a way of winning political parties in gaining the power of legislative seats, this study specifically focuses on strategic issues marketing or the method used by the United Development Party in winning the election contestation by applying the concept of the Adman Nursal theory of push, pull, and pass marketing. This research uses a descriptive qualitative approach used to interpret the data in every book and informant who has conducted research on political marketing strategies. The results of this study revealed that the political marketing strategy adoptedby the PPP intheelection contestation did not provide an increase due to corruption cases that tarnished the name of the United Development Party so that there was adecline in votes in the 2019 elections. This did not rule out that for the placement of legislative seats the PPP gained three seats in Legislative power, by providing political education, utilizing cooperation with social media, and religious leaders in socializing through certain programs, this has become a way of increasing the existence of the 2019 United Development Party in the City of Tangerang.Keywords: Political Marketing Strategies, Legislative Power, Political Parties AbstrakPenelitian ini menggambarkan strategi marketing politik Dewan Pimpinan Cabang (DPC) Partai Persatuan Pembangunan (PPP) dalam memenangkan kontestasi pemilu, marketing politik yang dilakukan Partai Persatuan Pembangunan merupakan suatu cara kemenangan partai politik dalam mendapatkan kekuasaan kursi legislatif, Penelitian ini secara khusus berfokus pada masalah strategi marketing atau cara yang dilakukan Partai Persatuan Pembangunan dalam memenangkan kontestasi pemilu dengan menerapkan konsep teori Adman Nursal yaitu push, pull, dan pass marketing. Penelitian ini menggunakan pendekatan kualitatif deskriptif digunakan untuk menginterpretasikan data dalam setiap buku dan informan yang telah melakukan penelitian terhadap strategi marketing politik. Hasil penelitian ini mengungkapkan bahwa strategi marketing politik yang diterapkan oleh PPP dalam kontestasi pemilu tidak memberikan peningkatan akibat kasus korupsi yang mencemari nama Partai Persatuan Pembangunan sehingga terjadi penurunan suara dalam pemilu 2019, Hal ini tidak menutup kemungkinan bahwa untuk penempatan kursi legislatif PPP mendapatkan tiga kursi dalam kekuasaan dilegislatif, Dengan memberikan pendidikan politik, pemanfaatan kerja samadengan media sosial, dan tokoh agama dalam bersosialisasi melalui program tertentu, Hal ini menjadi suatu cara dalam meningkatkan eksistensi Partai Persatuan Pembangunan pemilu 2019 di Kota Tangerang.Kata kunci: Strategi Marketing Politik, Kekuasaan Legislatif, Partai Politik